2004
DOI: 10.1093/deafed/enh024
|View full text |Cite
|
Sign up to set email alerts
|

Accessing University Education: Perceptions, Preferences, and Expectations for Interpreting by Deaf Students

Abstract: This paper provides a brief review of the history of deaf education in Australia, Australian Sign Language (Auslan), and Auslan interpreting. A panel of Australian deaf university students from diverse linguistic and educational backgrounds provides insights into their perceptions of sign language interpreting provision in university lectures. They commented on their interpreting preferences after viewing two videotaped segments of university lecture interpretation, one demonstrating a predominantly free appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 15 publications
3
22
0
4
Order By: Relevance
“…In a study of sign language interpreting for deaf Rochester Institute of Technology (RIT) students, Marschark, Sapere, Convertino and Seewagen (2005) found that the students did not acquire as much information from lectures as their hearing peers even with experienced interpreters who were familiar to the students. In Australia, Napier and Barker (2004) conducted a study involving four deaf university students in a panel discussion about their perceptions of interpreting in lectures. These students reported that they never accessed 100% of a university lecture, with estimates of how much they understood through sign language interpreting ranging from 50-90% of lecture material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of sign language interpreting for deaf Rochester Institute of Technology (RIT) students, Marschark, Sapere, Convertino and Seewagen (2005) found that the students did not acquire as much information from lectures as their hearing peers even with experienced interpreters who were familiar to the students. In Australia, Napier and Barker (2004) conducted a study involving four deaf university students in a panel discussion about their perceptions of interpreting in lectures. These students reported that they never accessed 100% of a university lecture, with estimates of how much they understood through sign language interpreting ranging from 50-90% of lecture material.…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study investigating the transition to tertiary education of eleven deaf and hard of hearing students found that many believed that they had been unprepared for the hearing-related difficulties they encountered at colleges of Technical and Further Education (TAFE) or university (McLean, Osborne, McAuliffe, Housden, & Revens, 1999). Like the other two Australian studies cited above (Komesaroff, 2005;Napier & Barker, 2004), the study involved relatively few deaf and hard of hearing participants.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that preservice teachers may not recognise that deaf students, like ESL students, have a unique language and a unique culture. It is important for teachers to know that Auslan is a complete and distinct language that is not only very different to English, but quite different to spoken languages altogether (Napier & Barker, 2004).…”
Section: Implications For Educatorsmentioning
confidence: 99%
“…In Australia, the majority of children with any degree of hearing loss are included in mainstream classrooms whether they rely on speech-reading, residual hearing, or sign language (Hyde, 2004;Napier & Barker, 2004). Deaf students who use Australian Sign Language (Auslan) as their first language are likely to have similarities to other students who are learning English as a second language (ESL), since both groups of students attend classes that are not in their primary language.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, few scientific studies have been conducted on deaf and hard of hearing university students. Those existing ones have focused on variables such as academic performance (Lang, 2002;Napier & Barker, 2004;Richardson, Barnes & Fleming, 2004;Richardson, Long & Foster, 2004;Richardson, MacLeod-Gallinger, McKee & Long, 2000). Furthermore, we were unable to identify scientific studies that had confirmed "the effectiveness of indicators of relevant actions and good practice concerning equality of opportunity in higher education for people with disability, that would enable progress in the formulation of standards for programmes and services aimed at university students with disability" (Alonso & Díez, 2008: 82).…”
Section: Introductionmentioning
confidence: 99%